(untitled) (International Journal of Engineering and Computer Science, 2015)
Ontology is defined as conceptual representation data and relationships between this data.In this paper, we propose to use this ontology for summarization of multiple documents related to a specific domain. We explore various techniques that can be used for summarization. We then focus upon a particular approach for summarization of documents belonging to a particular domain.The domain that we have considered is disaster management.As an example we will be taking the earthquake that took place in Nepal in April 2015.Using this example we will demonstrate summarization of multiple documents.